Pancreatic disease, panniculitis, polyarthrtitis syndrome successfully treated with total pancreatectomy: Case report and literature review. (2016) - Ferri, Valentina; Ielpo, Benedetto; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Caruso, Riccardo; Malave, Luisi; Plaza, Carlos; Rodriguez, Silvia; Garcia, Lina; Perez, Virginia; Quijano, Yolanda; et al.
Highlights: PPP (pancreatic disease, panniculitis, polyarthritis) syndrome is a rare disease caused by pancreatitis or pancreatic cancer. Panniculitis and polyarthritis are the main characteristics of the syndrome. A high mortality rate and chronic sequel are reported. Surgical and endoscopic treatment may improve the prognosis of this condition. Abstract: Introduction: Pancreatic disease can be complicated by extrabdominal manifestations such as panniculitis and polyarthritis. The symptomatic triad comprising pancreatic disease, panniculitis and polyarthritis is also known as PPP syndrome and is characterized by severe chronic sequels and high mortality rate. We describe a case of PPP syndrome successfully treated with spleen preserving total pancreatectomy; in addition we performed a literature review. Presentation of case: A 67 years old male presented panniculitis and polyarthritis without clinical abdominal symptoms. Clinical presentation, laboratory values and radiological findings demonstrated an acute pancreatitis and a pancreatic cancer was suspected; failure of conservatory treatments and high suspicious of malignancy led to perform a spleen preserving total pancreatectomy. Finally histological examination excluded a pancreatic cancer and confirmed a chronic pancreatitis. Patient was discharged with complete resolution of the extrabdominal disease. Discussion: In literature only 64 cases of PPP syndrome have been reported. Abdominal symptoms do not often appear at presentation and diagnosis may be delayed. Panniculitis develope in any part of the body but especially on the distal parts of the lower extremities, around the ankles and pretibial regions of the legs. Between osteo-articular manifestations polyarthritis is the most common one, although oligoarthritis, and monoarthritis in have been reported. Conclusion: PPP syndrome is a rare disease with a high mortality rate. A timely diagnosis and an aggressive treatment may improve the prognosis of this condition.